Muhammadiyah; Modern Thinking and Progress - Trisno Trisno (Universitas Muhammadiyah Malang, 2024)
This research explores modern Muhammadiyah thought and the development of its role in the social, religious and educational context in Indonesia. Muhammadiyah, founded by K.H. Ahmad Dahlan in 1912, was one of the Islamic organizations that pioneered the renewal of Islamic thought by prioritizing rationality, education and social charity. This article analyzes the basic principles of modern Muhammadiyah thought, such as the purification of Islamic teachings from the practices of superstition, heresy and khurafat, as well as the integration of religious values ​​with the dynamics of modern progress. Using a qualitative approach, this research highlights how Muhammadiyah formulates strategies in facing global change through education, health and economic development of the community. The findings show that Muhammadiyah has succeeded in maintaining its relevance as a modern Islamic movement by building a progressive network of educational institutions, health services and charitable businesses. This study also identifies the challenges faced by Muhammadiyah in maintaining the values ​​of moderation amidst various social and political dynamics in Indonesia. The results of this research contribute to understanding how Muhammadiyah realizes modern ideas in building an inclusive and dynamic Islamic civilization.